Gender differences in ischemic heart disease among the Middle-Eastern population - Alsaddah, Jadan J; Al Mutairi, Mohammad; Denić, Ljiljana Marković; Subha, Remya Pushparajan; Ašanin, Milika; Vasiljević, Zorana (Vojnosanitetski pregled, 2021)
Background/Aim. Despite substantial improvements in the outcomes of ischemic heart disease (IHD) in women, it continues to be the leading cause of morbidity and mortality. This paper aimed to study the gender-based differences among the Middle-Eastern population presented with IHD. Methods. This was a prospectively designed study where IHD patients who had an indicated coronary angiography (CA) performed at the tertiary cardiac center between 1st September 2014 to 1st September 2015 were analyzed. IHD patients were classified into two groups: stable IHD (SIHD) and acute coronary syndrome (ACS). Results. A total of 400 IHD patients had completed coronary angiographic data. About 70% of the patients were diagnosed with ACS and 30% with SIHD. Females were older (64 ± 12 years vs 59 ± 13 years, p < 0.004) and had higher body mass index (34 ± 7 kg/m2 vs 29 ± 5 kg/m2, p < 0.001) compared to males. Females were more diagnosed with hypertension (87% vs 62%, p < 0.001) and diabetes mellitus (76% vs 58%, p < 0.001) compared to males. Among patients with ACS, males tended to have more ST-elevation myocardial infarction (STEMI) (37% vs 12%, p < 0.001) whereas females presented more with non-STEMI (45% vs 17%, p < 0.001. Conclusion. Middle-Eastern females tended to have more adverse risk factors, presented more with non-STEMI, and had fewer rates of in-hospital complications.